Eksistensi Lapek Barajuik di Kalangan Masyarakat Pakandangan Kabupaten Padang Pariaman (International Forum of Researchers and Lecturers, 2025)
This research raises the theme of the existence of traditional Minangkabau food, specifically Lapek Barajuik among the Pakandangan community, to understand how well this food is currently thriving. The main question posed is how to maintain its existence amidst the advancement of the times. This research aims to describe the existence of this food and identify the obstacles faced by the community in enhancing its existence. The method used is qualitative research with a descriptive approach, through data collection from observation, interviews, and documentation. Data analysis was conducted through data collection, reduction, display, and verification. The research results show that Lapek Barajuik plays an important role in the culture of the Pakandangan community, known for its unique shape and taste, as well as being a symbol of identity and ancestral heritage. Although there is interest from the community, including the younger generation, this food faces challenges such as competition with modern foods, seasonal nature, and lack of technological utilization in promotion. In conclusion, the existence of Lapek Barajuik among the Pakandangan community, especially the older generation, is still preserved. They appreciate this food as an important part of the culinary tradition. Its appeal, especially its unique shape, creates a special impression when a son-in-law brings this food as a gift to the in-laws' house, making it symbolic in the family visit tradition. On the other hand, the interest of the younger generation in it has declined due to the abundance of modern food variations, although they still like this dish, as evidenced during certain events where Lapek Barajuik became a choice and was favored by the community.